1997
DOI: 10.1046/j.1365-2443.1997.1520350.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication profile of Saccharomyces cerevisiae chromosome VI

Abstract: Background: An understanding of the replication programme at the genome level will require the identification and characterization of origins of replication through large, contiguous regions of DNA. As a step toward this goal, origin efficiencies and replication times were determined for 10 ARSs spanning most of the 270 kilobase (kb) chromosome VI of Saccharomyces cerevisiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
161
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(178 citation statements)
references
References 38 publications
15
161
1
1
Order By: Relevance
“…Figure 1A and Supplemental Figure S4). At 2 h of meiosis, both Spo11-FLAG and Mre11-FLAG began to be localized in concert to an early replicating region of chromosome VI (Friedman et al, 1997;Yamashita et al, 1997;Raghuraman et al, 2001;Mori and Shirahige, 2007), including the very early mitotic and meiotic replication origins autonomously replicating sequences (ARS)606 and ARS607 (Figure 1, B and C). As premeiotic DNA replication further proceeded, they gradually localized to the chromosomal arm regions harboring comparatively late-replicating origins (Pearson r of signal log 2 ratio between Spo11-FLAG and Mre11-FLAG is 0.85 at 2 h and 0.72 at 3 h; Figure 1, B and C).…”
Section: Localization Of Spo11 To Chromosomal Arms During Premeiotic mentioning
confidence: 99%
“…Figure 1A and Supplemental Figure S4). At 2 h of meiosis, both Spo11-FLAG and Mre11-FLAG began to be localized in concert to an early replicating region of chromosome VI (Friedman et al, 1997;Yamashita et al, 1997;Raghuraman et al, 2001;Mori and Shirahige, 2007), including the very early mitotic and meiotic replication origins autonomously replicating sequences (ARS)606 and ARS607 (Figure 1, B and C). As premeiotic DNA replication further proceeded, they gradually localized to the chromosomal arm regions harboring comparatively late-replicating origins (Pearson r of signal log 2 ratio between Spo11-FLAG and Mre11-FLAG is 0.85 at 2 h and 0.72 at 3 h; Figure 1, B and C).…”
Section: Localization Of Spo11 To Chromosomal Arms During Premeiotic mentioning
confidence: 99%
“…Importantly, the ability of 2D gel assays to discriminate between active (bubble arc) and passive replication (Y arc) revealed that most of the yeast origins are intrinsically inefficient, as they fire in only a fraction of the cell cycles. Later on, extensive analyses of chromosomes III and VI by 2D gel electrophoresis confirmed that the budding yeast genome contains an excess of replication origins (Friedman et al 1997;Yamashita et al 1997). As for other eukaryotes, S. cerevisiae origins vary both in their timing and efficiency of initiation.…”
Section: Dna Replication Programs: the Yeast Paradigmmentioning
confidence: 99%
“…Each origin of DNA replication is strictly controlled to fire only once in the cell cycle in the fixed sequential order (1,2). This temporal program for origin firing is utilized for the maintenance of genome integrity through DNA replication checkpoint mechanism (3,4).…”
mentioning
confidence: 99%
“…It contains ten ARSs, ARS601-609, of which nine ARSs are active as replication origins that comprise five active replicons in mitotic S-phase (1,2,15). Thus, three origins (ARS605, 606, and 607) are used in high frequency, four (ARS601/2, 603, 603.5, and 609) are in intermediate frequency, and two (ARS604 and 608) are in low frequency, less than 5% of cell cycles.…”
mentioning
confidence: 99%
See 1 more Smart Citation